Chemotherapeutic Agents: Taxol and Vincristine Isolated from Endophytic Fungi - Makky, Essam A.; Manaf, Almatar (In-IJCPR, 2015)
Endophytic fungi are abundant and have been found asymptomatically in most plants species. Endophytic fungi are considered as hidden members of the microbial world and represent an under-utilized resource of natural bioactive compounds for agricultural, industrial and medicinal uses. As reported previously, several valuable natural products with anticancer, antimicrobial, and insecticidal properties have been successfully extracted from the endophytic fungi. Chemotherapy yields the first promise of destroying cancer cells that has distributed into the body. This is due to the fact that chemotherapeutic agents overlap with the process of dividing cancer cells, which in turn leads to establishing new cells. Vincristine (vinca alkaloids) and podophyllotoxin prohibit the microtubules polymerization at high drug concentrations whereas Taxol™ and Taxotere stimulate the microtubules polymerization and stabilize the microtubules as well at high concentrations. In This review, we critically attempt to summarize the mechanisms of the cancer chemotherapeutic drugs, namely, Taxol and Vincristine (vinca alkaloids) on the need for more the research in the field of cancer chemotherapy.